STUDIES ON THE EFFECT OF POSTHARVEST FACTORS ON PLANTAIN QUALITY (1992)
This study was undertaken to evaluate the social and technical factors affecting plantain handling in Nigeria, with a view to recommending measures of minimising losses and improving product quality. Questionnaires on the effect of production, transportation and marketing practices on postharvest losses were administered to farmers, transporters and traders respectively in a survey of three plantain producing States and one non-producing State in Nigeria. Based on the findings of this survey, physical characteristics of plantain which are likely to change as the plantain matures were investigated using two cultivars of plantain namely, Agbagba, a false horn type and Obino l'ewani, a French type, harvested between 8 to 14 weeks after anthesis, to obtain indicators for determining harvest maturity. Also, a methodology for measuring qualitative and quantitative losses in plantain was development. In addition, the effect of maturity at harvest, packaging and the Vibration experienced during transportation on mechanical damage were investigated in simulated transit studies, as well as selected quality attributes of processes products from the Agbagba plantain harvested between 8 to 12 weeks after anthesis, in Order to establish Optimum handling conditions for plantain for the distribution and Processing outlets. The measurement of finger weight and finger length have been developed as new objective and non-destructive methods for harvest maturity determination in plantain cultivars. It was also observed that the measurement of bruise area on the peel and percentage weight loss were associated with aesthetic quality, whilst the measurement of trimming losses on the pulp was a good indication of quantitative losses and the number of days to full ripening was an indication of the storage life of the two cultivars. Harvesting at the immature stage increased the susceptibility of the plantains to underpeel bruising leading to significantly (p = 0.05) higher trimming losses and weight losses in the two cultivars. Lining the packaging Containers with polyethylene reduce the damage significantly. The sensory quality of flavour and texture were affected by the stage of maturity at the time of harvest. Chips and ’dodo' prepared from immature plantain scored significantly (p = 0.05) lower points than mature ones. Even though it might be adviceable to harvest plantain at an immature stage in Order to extend its green-life, this work clearly shows that this would be at the expence of quality.